"People love talking about racism": downplaying discrimination, and challenges to anti-racism among Eritrean migrants in Australia. Issue 5 (4th April 2023) - Ben, Jehonathan
ABSTRACT: Why may the supposed victims of racism and discrimination downplay these phenomena? This paper examines experiences of and responses to racism and discrimination among highly educated Eritrean migrants in Australia. Contrary to research findings on experiences of discrimination among migrant groups as widely reported and impactful, most of my interlocutors seldom reported such experiences, despite acknowledging that discrimination existed generally and vicariously. I discuss participants' direct and indirect experiences with racism and discrimination, and identify five key reasons for downplaying and not reporting them, including limitations to perceiving and recognizing these phenomena; undermining racism in Australia in comparison to other racisms; gratitude to Australians and to Australia as "the lucky country"; harbouring strong meritocratic values that contrasted with viewing discrimination as impactful; and dissociation from narratives of victimhood and powerlessness. Finally, I discuss how participants' perspectives pose challenges for anti-racism scholarship and practice more broadly.